ALKITAB DAN HUBUNGAN PERTEMANAN KAJIAN TEOLOGI PENTAKOSTA MEMAKNAI HUBUNGAN PERTEMANAN DALAM ALKITAB: Pentecostal Theology Studies Meaning Relationships in the Bible - Kosma Manurung (Vox Dei: Jurnal Teologi dan Pastoral, 2021)
This article intends to interpret the relationship of friendship in the Bible in the study of Pentecostal theology. The method used in this article research is text analysis and literature review. This article discusses three examples of friendship relationships, namely the friendship of David and Jonathan, Daniel and his three friends, and Paul and Silas. Based on the results of this article's research, friendship is built on commitment, self-sacrifice, and flock loyalty. The purpose of God designing friendship relationships is as a divine community through which believers get strength and confirmation so that they have an impact on the Kingdom of God.